INTERDISCIPLINARY CONNECTIONS OF ENGINEERING DISCIPLINES AS A MEANS OF IMPROVING THE QUALITY OF PERSONNEL TRAINING IN HIGHER EDUCATION - S,Negmatullayev; B.Ergashov; A.Bobamatov; A.Akbarov; A.Maxmudov; X.Ortiqov (Scientific Impulse, 2024)
The article considers the issues of interdisciplinary connections of engineering disciplines as a means of improving the quality of training in higher education. The main types of interdisciplinary connections between technical and engineering disciplines are listed.